2013
DOI: 10.1177/0885412213510524
|View full text |Cite
|
Sign up to set email alerts
|

Historic Preservation and Urban Revitalization in the Twenty-first Century

Abstract: Historic preservation is largely an urban profession with strong ties to city planning and development. Advocates tout preservation as a key driver of urban revitalization, but there remains a dearth of empirical research that addresses this intersection. This article reviews the current state of affairs in preservation practice and scholarship and builds new connections with four leading discourses in urban revitalization: the New American City, place matters, anchor institutions, and legacy cities. We call f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 99 publications
(152 reference statements)
1
45
0
Order By: Relevance
“…According to Yuen (2005) urban conservation produces civic pride and economic benefit as the uniqueness of cultural heritage increases urban capability of existing or performing in harmonious or congenial combination. Furthermore, Ryberg-Webster and Kinahan (2013) demonstrated the capability of heritage preservation "as an agent of urban change" and as a "facilitate[or for] community and economic development" (p. 119). Therefore, striking a balance between heritage conservation and urban development, targeting sustainability, is now the main challenge in growing cities (Stovel, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…According to Yuen (2005) urban conservation produces civic pride and economic benefit as the uniqueness of cultural heritage increases urban capability of existing or performing in harmonious or congenial combination. Furthermore, Ryberg-Webster and Kinahan (2013) demonstrated the capability of heritage preservation "as an agent of urban change" and as a "facilitate[or for] community and economic development" (p. 119). Therefore, striking a balance between heritage conservation and urban development, targeting sustainability, is now the main challenge in growing cities (Stovel, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…216-217;Birch & Roby, 1984;Listokin, Listokin, & Lahr, 1998;Laurie, 2008). Furthermore, historic preservation offers intrinsic social benefits to communities because of the retention of local heritage (Yung & Chan, 2012, p. 355;Ryberg-Webster & Kinahan, 2013;Barthel-Bouchier, 2013;Bullen & Love, 2010, p. 216;Frey & Bowdon, 2012;Langston, 2008).…”
Section: Sustainability and Adaptive Reusementioning
confidence: 99%
“…Ryberg-Webster and Kinahan (2013) offer an extensive literature review of historic preservation's role in urban revitalization, specifically describing how historic preservation can spur economic development and housing production. Scholars have suggested that historic preservation based-initiatives have achieved greater success in revitalization than urban renewal strategies that often involved raising old neighborhoods (Birch & Roby, 1984, pp.…”
Section: Urban Revitalization and Smart Growthmentioning
confidence: 99%
See 2 more Smart Citations